Evaluasi Promosi Penggunaan Kondom untuk Mencegah HIV/AIDS di Lokalisasi Pelacuran di Kabupaten Banyuwangi - Hafrida Ira Paramastri, Agus Priya (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: HIV/AIDS in East Java in the year of 2005 is the third highest disease in Indonesia. The district of Banyuwangi is the third rank in Indonesia after Surabaya and Malang in terms of the case number. The biggest patient group of HIV/AIDS is sexual worker women (WPS). Various health promotion programs in using condom have been implemented although the case of AIDS still tends to improve.Objective: This research was aimed to obtained description on health promotion program implementation by using condom in the prevention of HIV/AIDS in the localization of prostitution from the perspective of those who obtained the health promotion and who conveyed the health promotion.Method: This was an emic qualitative research. The main informant was WPS which was supported with informant of client, procurers, government and NGO. The research was implemented in the localizations of Banyuwangi district. Data was collected by using in-depth interview and observation for comparing the result of in-depth interview. Data was analyzed by using constant comparative method and data validity was using source and triangulation method.Result: The subjects did not comprehend HIV/AIDS appropriately. Their negotiation skill was low as they were more prioritized on the sales result of the sexual relationship. The promotion media that were sticker, poster and advertisement were not really interesting, as they were not appropriate for localization. Interpersonal supervision by health care provider and the check up of reproductive health was not successful. Promotion through selling condom in parking place, condom promotion and condom ATM was able to remind the WPS to be more aware on the transmission of the disease and in using condom. Media of film was also preferred. It is suggested for program modification is by adding up the health promoter from other related institution. Government plays a role in giving the budget of HIV/AIDS prevention program.Conclusion: Various promotion media was not suitable with the need in localization (sticker, poster, booklet), while other media could influenced to remind the prevention of HIV/AIDS transmission (promotion in parking place, condom promotion, supervision of the health care provider). Negotiation in using condom was still low. The continual supervision of health care provider and the promotion in the parking place were expected could be disseminated and continued.Keywords: promotion evaluation, condom, HIV/AIDS, prostitution